Propuesta de un manual de buenas prácticas de manufactura en la corporación CASA S.A. - Alvarez Delgado, Iván Sebastián (2018)
The present good manufacturing practice Manual was made in Tanicuchi parish in the Casa corporation, it is a company dedicated to the production of Andean lupin without bitterness, this has a good acceptance in the marketplace, for this reason there are a commitment with the consumer and want to improve constantly the quality and harmlessness of the product implementing the GMP Manual and the Operational Procedures of Sanitation Standards (OPSS). Is considered that it is a basic tool for the obtaining of harmless and secure products for the human consume, in this Manual we focused on the hygiene and the manipulation way, contributing to the assurance of a secure, healthy and harmless food production. It is clear that the rest is even higher for the small companies that are located in the countryside, because the adverse conditions, the infrastructure, sanitation, transport and lack of companies, the whole responsibility falls in only one person who should assume as he or she can in every that regards to the production and merchandising to which would be added the requirements respecting to harmlessness and quality. The Manual has been structured in such a way that the reader can not only comprehend the objectives that are followed with the good practices but also the reader can put them into practice, the guide also provides some examples regard to documentation, which is identified as one of the main weaknesses in the implementation of harmlessness and quality management systems, with the purpose of ease a referent point for a labor that should be attended and tailored to the “CORPOCAS” company.